Microphysical Pathways Active Within Thunderstorms and Their Sensitivity to CCN Concentration and Wind Shear. Issue 5 (1st March 2023) - Barrett, Andrew I.; Hoose, Corinna
Abstract: The impact of cloud condensation nuclei (CCN) concentration on microphysical processes within thunderstorms and the resulting surface precipitation is not fully understood yet. In this work, an analysis of the microphysical pathways occurring in these clouds is proposed to systematically investigate and understand these sensitivities. Thunderstorms were simulated using convection‐permitting (1 km horizontal grid spacing) idealized simulations with the ICON model, which included a 2‐moment microphysics parameterization. Cloud condensation nuclei concentrations were increased from 100 to 3, 200 CCN/cm 3, in five different wind shear environments ranging from 18 to 50 m/s. Large and systematic decreases of surface precipitation (up to 35%) and hail (up to 90%) were found as CCN was increased. Wind shear changes the details, but not the sign, of the sensitivity to CCN. The microphysical process rates were tracked throughout each simulation, closing the mass budget for each hydrometeor class, and collected together into "microphysical pathways, " which quantify the different growth processes leading to surface precipitation. Almost all surface precipitation occurred through the mixed‐phase pathway, where graupel and hail grow by riming and later melt as they fall to the surface. The mixed‐phase pathway is sensitive to CCN concentration changes as a result of changes to the riming rate, which were systematically evaluated. Supercooled water content was almost insensitive to increasing CCN concentration, but decreased cloud drop size led to a large reduction in the riming efficiency (from 0.79 to 0.24) between supercooled cloud drops and graupel or hail, resulting in less surface precipitation. Plain Language Summary: The amount of rain and hail from thunderstorms can be influenced by the amount of pollution in the form of aerosol particles, which determine how many cloud droplets form and how large they are. Unfortunately, different numerical models give different answers on whether rain and hail increase or decrease if pollution increases. In this article, we present a new analysis method helping to identify the small‐scale processes which are responsible for the increase or decrease in a specific numerical scheme. We apply it to simulations of thunderstorms and show that the decrease of rain and hail in the numerical model used here is mostly linked to the riming process. Riming is the collision of cloud droplets and frozen particles at temperatures below 0°C, such that the liquid water freezes to the surface of the ice particles and makes them bigger. Less riming occurs when pollution increases, because cloud droplets are smaller. This process is very important because nearly all rain reaching the surface consists of melted ice particles. Key Points: Microphysical pathways are constructed by tracking microphysical processes rates and closing the hydrometeor mass budget More cloud condensation nuclei lead to less surface precipitation and hail, due to smaller cloud drop sizes and reduced riming collection efficiency Simulations with constant riming collection efficiency reveal two different hail formation pathways